Preliminary results on the Gaulish terra sigillata from the fish-salting production centre at Tróia - Magalhães, A. P. (2021)
The fish-salting production centre at Troia received various imports of terra sigillata from the 1st century to the 6th century. Although it did not reach the significance of the African Red Slip Ware, Gaulish Sigillata is the second most important group of imports of this category on this archaeological site. The recognition of a Tiberian foundation level with Gaulish vessels dates the arrival of this tableware. Nevertheless, we agree with the assumption of previous studies that the majority of the pieces from this assemblage corresponds to the Claudian period onwards. The purpose of this paper is to present the current state regarding terra sigillata studies at Troia, more precisely related to the Gaulish productions and their significance in the largest fish-salting centre of the Roman Empire.